Enhancing Police Accountability: The Role and Challenges of Itwasum POLRI in Institutional Supervision - Efendi Sianipar, Ricky; Oktavia Sadipung, Theresia (Dinasti International Journal of Digital Business Management, 2025)
The Inspectorate of General Supervision (Itwasum) of the Indonesian National Police (POLRI) serves as the internal control mechanism to ensure accountability, transparency, and efficiency in policing. This study examines the roles, methodologies, and outcomes of Itwasum POLRI in enhancing institutional integrity and addressing organizational challenges. Using a qualitative approach, data was collected through policy document analysis, interviews with relevant stakeholders, and a review of secondary literature. The findings reveal the critical impact of Itwasum POLRI's oversight on institutional reforms, resource management, and public trust. However, challenges persist in terms of bureaucratic resistance, limited resources, and technological adaptation. Recommendations include strengthening legal frameworks, increasing resource allocation, and adopting digital solutions for improved oversight.